Production and Characterization of Crop Residues Derived Biochars for Soil Amendment and Carbon Sequestration - Lompo, Désiré Jean-Pascal; Yé, Lambiénou; Ouédraogo, Souleymane; Sori, Siélé Ibrahima; Nacro, Hassan Bismark (Journal of Agricultural Studies, 2021)
This study focused on the production and characterization of biochars from three types of crop residues comprising cotton stems, corn cobs and sorghum stems. The reactor used was a local cone kiln made from a 200-liter drum. The production parameters measured included the duration of pyrolysis, the amount of biochar produced and the production yield. The chemical characteristics of the biochars were determined using the usual analytical methods used for organic amendment analyses. According to the study, pyrolysis time, biochar quantities and production yields depended on the type of crop residues. The three types of biochar obtained showed high C/N values indicating that their use as soil amendment must be combined with mineral fertilizers to ensure good plant development and crop yield. The heavy metal contents of the three biochar types complied with the international standards recommended for biochars by the International Biochar Initiative (IBI) and by the European Biochar Certificate (EBC). The production and the use of Biochar from crop residues is an interesting alternative for sustainable soil fertility management in the Sahelian countries.